The application of single cell gel electrophoresis or comet assay to human monitoring studies - Valverde Mahara; Ostrosky-Wegman Patricia; Rojas Emilio; Fortoul Teresa; Meneses Fernando; Ramírez Matiana; Díaz-Barriga Fernando; Cebrian Mariano (Salud Pública de México, 1999)
Objective. In the search of new human genotoxic biomarkers, the single cell gel electrophoresis assay has been proposed as a sensible alternative. Material and methods. This technique detects principally single strand breaks as well as alkali-labile and repair-retarded sites. Results. Herein we present our experience using the single cell gel electrophoresis assay in human population studies, both occupationally and environmentally exposed. Conclusions. We discuss the assay feasibility as a genotoxic biomarker.